Synthesis and Characterization of Vertosin Schiff Base with Temperature and Time Optimization (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Perfume is a product designed to mask or eliminate unpleasant odors and impart a pleasant fragrance to the body, rooms, or various objects. One synthetic ingredient commonly added to fragrances is a schiff base, a compound formed through a condensation reaction between an aldehyde and an amine. Schiff bases enhance the chemical and thermal stability of fragrances due to their distinctive and long-lasting aroma. One such compound, vertosin, is known for its strong green, citrus, and herbal scent and is suitable for personal care products. This research aimed to synthesize vertosin via a condensation reaction between triplal and methyl anthranilate under varying temperatures and durations, and to characterize the resulting product using Gas Chromatography-Mass Spectrometry (GCMS). The study employed a combination research method consisting of synthesis, characterization, and data analysis. The synthesis was conducted at temperatures of 90, 100, and 110°C for 30 and 60 minutes. Characterization included organoleptic tests (color and odor), density and specific gravity measurements, and compound confirmation using GCMS. Data analysis was performed using two-way ANOVA. The results showed that the optimal condition for vertosin synthesis was at 110°C for 60 minutes, yielding the highest concentration. Mass spectrometric fragmentation patterns confirmed the product as methyl 2-[[(E)-2,4-dimethyl-1-cyclohex-3-enylidene)methyl]amino]benzoate with a molecular weight of 271 g/mol. The synthesized vertosin had a green, lily, orange blossom, fruity, floral scent, an orange color, and average density and specific gravity values of 1.092 and 1.094, respectively, which were in accordance with standard specifications.